STUDI EKSPERIMEN KUAT TEKAN BETON NON AGREGAT KASAR SEMEN PCC DENGAN SIKAMENT LN - Siregar, Derina Ika Kumalasari; Mungok, Chrisna Djaya; Samsurizal, Eddy (JeLAST : Jurnal PWK, Laut, Sipil, Tambang, 2014)
This paperpresents the results ofthe use ofthe added materialismixed into theSikamentLN mortarbymixingvaryinglevels of0.6%, 1%, 1.5%. Specimensmade​​cuboidwith a length of5cm, width5cmand height5cm. Aimstodetermine how much influencethe addition ofvariantsSikamentLN0.6%, 1%, and1.5% in thecompressive strengthof mortarbasedfunctionsthat usecementPCCage. job mix formula refers to the ratio of cement to fine aggregate (sand) is a standard ASTM C 109 / 109m - 02 "Standard Test Method for Compressive Strength of Hydraulic Cement mortars", with a ratio of 1 Pc: 2.75 Ps: 0.485 water. From the research, the compressive strength characteristics of mortar 28 days using sikament LN (0.6%, 1.0%, 1.5%), Characteristic compressive strength of each specimen variation of 28 days in a row to reach (28.51 MPa; 26.77 MPa, and 26.55 MPa) while the characteristic compressive strength of 27.66 MPa mortar without the additive. Keywords: Mortar, compressive strength, SikamentLN, CementPCC